DNS analysis of turbulent vaporizing two-phase flows, Part I: Topology of the velocity field. (November 2022) - Onofre Ramos, Marcos Martín; Zhao, Song; Bouali, Zakaria; Mura, Arnaud
Abstract: This work is devoted to the characterization of turbulence in two-phase flows with mass transfer. The objective is to provide further insights into the influence of liquid/gas interfaces on some statistical characteristics of the fluctuating velocity and scalar fields collected in the gas phase. The first part of this study is primarily focused on the velocity field. Thus, turbulence topology is educed from the consideration of the invariants of the Reynolds stresses, velocity gradients, strain-rate, and rotation tensors. This analysis is completed by some geometrical and alignment statistics. The corresponding quantities are studied using a set of direct numerical simulation (DNS) databases featuring two distinct values of the liquid volume fraction ϕ ℓ . The starting point is the transport equation for the mixture fraction. In most descriptions of two-phase flow combustion, it is indeed used to characterize the multi-component mixture. However, considering the non-linear dependence of chemical reaction rates to composition, the single knowledge of its mean (or filtered) state is insufficient to describe turbulent conditions. Its variance and associated mean (or filtered) scalar dissipation rate (SDR) must be evaluated, with the latter quantity (i.e.,  the SDR) driven, at leading order, by the velocity gradients relevant to straining effects and by the curvature of the mixture fraction field. The present statistical analysis makes use of conditional sampling based on a level-set value which signs the distance to the interface, thus allowing to discriminate its influence on the velocity gradients and associated turbulence topology. Highlights: Direct Numerical Simulation (DNS) of turbulent two-phase flows are conducted. A detailed investigation of the turbulence topology is performed. It is modified as the liquid/gas interface is approached. Isotropic turbulence evolves towards a one-dimensional-turbulence state. Enhancement of transfer and vortex-stretching is observed in this zone.